EFFECTS OF AUDIT INTERNAL PERFORMANCE MEASURES, PROFESSIONAL EXPERTISE, AND INTERNAL AUDITOR WORK EXPERIENCE ON UNIVERSITY PERFORMANCE - Roza Mulyadi; Ahyakudin Ahyakudin; Mukhtar Mukhtar (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2019)
The purpose this research is to research influenc of internal audit performance measures, professional expertise and auditor work experience  towards state universities in Banten. The population in this study were auditors of the Internal Audit Unit (SPI) at State Universities in Indonesia. The research sample is the SPI auditor and the former State University SPI auditor in Banten. Data collection is done by coming directly to the SPI auditor and former auditor of State University SPI in Banten. This research was conducted by survey method through a questionnaire to SPI auditors and former SPI auditor of State University in Banten. Total of State Universities in Serang is 4 universities. From the survey result, the number of SPI auditors at State University in Banten is 117, consisting of 73 former SPI auditors and 44 SPI auditors. So, the number of distributed questionnaires same as proportion of total samples or respondents is 117 questionnaires. Data processing until hypothesis testing in this study uses SPSS. The results of this study are (1) size of internal audit performance has a significant positive effect on university performance, (2) professional expertise has no significant positive effect on university performance and (3) work experience of internal auditors has a significant effect on university performance.